Colocephalectomy for the Treatment of Capital Physeal Fracture of the Femoral Head in Pony - Lorga, Andressa Duarte; Dornbusch, Peterson Triches; Gomes, Anny Raissa Carolini; Cocco, Mariana; Amaro, Flávia do Prado Augusto; Schade, Jackson; Deconto, Ivan; de Barros Filho, Ivan Roque (Acta Scientiae Veterinariae, 2020)
Background: Femoral capital physeal fractures occur in young animals and are generally associated with trauma. They have a poor prognosis and surgical therapy is the most indicated. There are few studies describing surgical treatment and postoperative results, so the objective of the present report was to present the first case in Brazil of a colocefalectomy for the treatment of femoral capital physeal fracture in a young pony, the post-surgical and the results obtained with the technique employed. Case: An 18-month-old pony, male, not castrated, , weighing 136 kg was referred to the Veterinary Hospital of the Federal University of Paraná (HV-UFPR) with a history of trauma for 4 days. On physical examination, the animal presented lameness grade 5 of the right pelvic limb, shortening and lateral deviation of the limb, crackling and painful sensation on abduction, and slight atrophy of the gluteal muscles on the affected side. In the radiographic examination, a femoral capital physeal fracture was found in the oblique ventro-dorsal projection. Once the diagnosis was performed, a colocefalectomy was realized, as the patient is a light and short horse. The patient underwent general anesthesia and was placed in the left lateral position. The access to the coxofemoral joint was made through the lateral face of the right hindlimb. The muscles of the region were incised and deviated, so a partial myotomy was performed in the deep gluteal and vastus lateralis. This procedure allowed to visualize the fracture, where the head of the femur remained congruent to the acetabulum. A hammer and a curved osteotome were used to section the round ligament, allowing the dislocation of the femoral head and with the aid of an oscillating orthopedic saw was performed the femoral neck ostectomy. Previously to the synthesis of the muscular planes and the skin, a passive tubular drain was fixed, in order to avoid the accumulation of exudate and consequent dehiscence of stitches, which was removed on the 6th postoperative day. For postoperative analgesia, epidural morphine was administered for 6 days and intravenous phenylbutazone for 3 days. Antibiotic therapy was performed with Ceftiofur and Metronidazole. The stitches were removed on the 15th postoperative day, after the correct healing of the surgical wound. The patient’s return to activity was gradual and he was pasture sound on the 42nd postoperative day. After medical discharge, contact with the owner was kept until the fifth postoperative month, and he related that the animal remained walking well and maintaining his reproductive function. Discussion: Femoral capital physeal fractures can occur in young animals, and are not common in clinical surgical care. Clinical signs are crackle of the joint on manipulation and presence of swelling in the affected region. The patient in question, in addition to evident lameness, had crackling and painful sensation during the abduction of the limb, but there was no local swelling, but an atrophy of the musculature of the limb, that occurs in cases of chronic femoral injury. Surgical intervention is the indicated method of treatment and should be performed as soon as possible after the injury has occurred, avoiding the worsening of bone and joint degeneration. Femoral head ostectomy is more suitable for animals less than 12 months old and weighing up to 100 kg. The technique has as a postoperative complication the contamination of the surgical wound, however the implantation of the passive tubular drain allowed rapid evolution of healing. Physical rehabilitation in the postoperative period is variable according to the progress of the animal’s locomotion. Therefore, the colocefalectomy technique aims to maintain the patient’s quality of life, even as in the case reported, it allowed the animal to maintain the reproductive function.